Investigation of pure-cubic optical solitons in nonlinear optics - Rehman, S. U.; Bilal, M.; İnç, Mustafa; Younas, U.; Rezazadeh, H.; Younis, M.; Mirhosseini-Alizamini, S. M. (Springer, 2022)
The primary focus of this article is on cubic optical solitons (os) in a polarization-preserving fiber modeled by the nonlinear Schrodinger equation (NLSE). In this work, our main idea is to secure a variety of optical solitons in the forms of hyperbolic and trigonometric solutions, as well as a class of solitary wave solutions such as dark, bright-dark, singular, singular periodic, multiple-os, and mixed complex soliton solutions. To examine the governing model, a recently created integration technique called as the new extended direct algebraic method (NEDAM) is used. Furthermore, the investigated equation is explained in terms of two forms of nonlinearity. The constraints conditions for the resulting solutions are explicitly presented. The obtained findings demonstrate that the applicable computing system is direct, productive, and trustworthy, and that it may be applied to more complex phenomena.
Keywords: Optical solitons; NEDAM; Refractive index; Integrability